Slit mesh technique in laparoscopic inguinal hernia repair: a retrospective analysis - Ozan M. Aydin; Yasin Kara; Serhan Yilmaz; Erkan Somuncu; Osman Sibic (Videosurgery and Other Miniinvasive Techniques)
Introduction: Slit mesh (SM) is a technical modification used in laparoscopic total extraperitoneal (TEP) inguinal hernia (IH) repair. It aims to reduce recurrence by improving mesh anchoring and preventing cranial migration. However, its clinical effectiveness remains controversial.